2009
DOI: 10.1002/col.20523
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing observer metamerism in display systems

Abstract: Observer metamerism has long been known to be an issue of concern for color engineers. With the advent and mass proliferation of narrow-band display devices, this article addresses the issue of observer metamerism and puts it in the context of first understanding the implication of interobserver variations in the color matching functions (CMFs) and additionally designing the ideal set of primary illuminant spectral power distributions (SPDs) such that observer metamerism is minimized. The article also suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Industry examples with high degrees of observer metamerism are soft proofing in graphic arts (previewing color pictures on monitors to predict press print colors) and color grading in digital cinema or television (color adjustment on test displays by comparison with a reference monitor). Furthermore, the issue is worsened if spectrally narrow stimuli are viewed . It is of interest to know how much CMFs differ between people and how much observer metamerism would be expected for a given application.…”
Section: Introductionmentioning
confidence: 99%
“…Industry examples with high degrees of observer metamerism are soft proofing in graphic arts (previewing color pictures on monitors to predict press print colors) and color grading in digital cinema or television (color adjustment on test displays by comparison with a reference monitor). Furthermore, the issue is worsened if spectrally narrow stimuli are viewed . It is of interest to know how much CMFs differ between people and how much observer metamerism would be expected for a given application.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this measure has been used to represent the primary coverage in order to evaluate the possibility of observer metamerism in displays [Ram09]. We propose a more general form of the FWHM metric which we call the Range at Weighted-Maximum (RWM) to accommodate multi-modal spectrum.…”
Section: Desired Characteristics Of the Chosen Primariesmentioning
confidence: 99%
“…Being able to measure this effect is particularly important not only to help users choose the right display for color‐critical applications but also to help manufacturers design new display technologies . Oicherman et al .…”
Section: Introductionmentioning
confidence: 99%
“…Being able to measure this effect is particularly important not only to help users choose the right display for colorcritical applications but also to help manufacturers design new display technologies. [3][4][5] Oicherman et al 6 studied the effect of observer metamerism (OM) on color matching of display and surface colors and suggested that traditional color-difference formulae such as CIEDE2000 can model it well. Aiming at developing a single index that allows to compare several displays, Long and Fairchild 7 proposed several indices to determine the sensitivity of a monitor to observer variability.…”
Section: Introductionmentioning
confidence: 99%